Christian ethics and HIV stigma: Solidarity, social responsibility and the golden rule - Germari Kruger; Eduardus A.J.G. van der Borght; Adriaan L. Rheeder (HTS Teologiese Studies/Theological Studies, 2025)
This article examines human immunodeficiency virus (HIV) stigma within South African Christian faith communities, where misconceptions linking HIV to moral failing persist. Employing an analytical approach, the study critically analyses Articles 13 (Solidarity and Cooperation) and 14 (Social Responsibility and Health) of The United Nations Educational, Scientific and Cultural Organization (UNESCO) Universal Declaration on Bioethics and Human Rights, alongside selected biblical narratives, to develop an ethical framework addressing stigma. Using a literature review methodology, it integrates these principles with the Christian ‘golden rule’ (Mk 12:28–34) and the African philosophy of Ubuntu, promoting compassion, acceptance and collective responsibility for people living with HIV. The framework aims to bridge global bioethical standards with local religious and cultural values. This study offers a unique contribution to Christian ethical evaluations of HIV stigma, emphasising solidarity and social responsibility as actionable responses.